Balance reactions of female basketball players after perturbation in the sagital plane - Ramazanoglu, N.; Tatar, Y.; Sayli, O.; Uzun, S.; Camliguney, F.; Cotuk, B. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The female basketball players studied were reported to suffer a significantly greater number of knee and ankle injuries than male basketball players. During team sport activities, planned change of movement direction allow the athlete to anticipate, which allow these postural adjustments to be made much more easily. However, in the case of unpredictable postural perturbations or cutting movements, postural adjustments are harder to make, which affects loading of the lower limb joints and muscles, and causes balance loss. Objective: To investigate displacement of center of foot pressure (COF), recovery time and leg muscle activity pattern after perturbation in the knee joint and to compare female basketball players with sedentary subjects. Method: Twenty six young female students: 11 elite basketball players (age= 17.55±.52 years, height=178.36±5.90 cm, weight=67.14±5.86 kg) with at least 3 training years and 15 sedentary subjects (age=17.47±.64, height=159.53±5.68 cm, weight=61.93±12.04 kg) were included in the study. Vertical jump was used to measure leg muscle strength. Assessment of balance was measured with Matscan (Tekscan, Boston, MA). The following balance tests were utilized: two feet eyes opened (EO), eyes closed (EC), right foot EO, and left foot EO both unperturbated and perturbated conditions. 13 N force was applied in the sagital plane (anterior- posterior (A/P) direction) to the knee joint in order to produce balance loss during perturbation. Surface EMG (DELYSIS) measurements were taken from the quadriceps femoris, biceps femoris and tibialis anterior and gastrocnemius muscle to examine the order of muscle activation during unanticipated perturbation. Results: Female basketball players legs were stronger than sedentary students (p<0.01). No differences were found for COF in both perturbated and unperturbated condition for two feet eyes opened (EO), eyes closed (EC), right foot EO, and left foot EO between female athletes and sedentary subjects. However, there were significant differences in terms of recovery time after perturbation (A/P direction) for two feet eyes opened (EO), eyes closed (EC), right foot EO, and left foot EO between the groups. Although female basketball players had longer height, athlete`s recovery time was shorter than their sedentary peers (p<0.05). There was no difference in EMG muscle activation pattern for leg muscles between two groups during two feet OE. Discussion: Short recovery time may be important in providing early defense against loss of balance during unanticipated perturbation in the game. Unexpected perturbation training facilities should be addressed as part of the player`s individualized program to improve postural balance.